The stability of nutritional composition and physical traits of chicken patty containing oyster mushroom packed with biodegradable and non-degradable packaging materials - Wan Rosli, W. I.; Solihah, M.A.; Shazwan, Z. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Extensive use of synthetic-based polymer plastic as packaging medium to pack food products has led to serious environmental problems due to their total non-biodegradability property. The stability of nutritional composition and physical traits of chicken patties containing oyster mushroom packed with biodegradable and non-degradable packaging materials were studied. The chicken patties containing oyster mushroom were packed with either biodegradable plastic (BP), paper box (PB) or non-biodegradable high density polyethylene (HDPE). Generally, there were no significant (P>0.05) different in all nutrient analyzed except for carbohydrate after 6 months of storage for chicken patties packed with different types of packaging. The chicken burger packed with both BP and PB packagings were able to retain the moisture and fat without jeopardizing the diameter reduction and cooking yield during storage. There were no differences in all nutrient analyzed after 6 months of storage of chicken patties packed with either biodegradable packagings (BP and PB) or non-degradable packaging. In addition, frozen storage does not significantly affect the concentration of of β-glucan in both BP and PB packagings. In summary, these results indicate that biodegradable packagings applied in packing chicken patty frozen for 6 months were effective in controlling the microbial growth and provide wholesomeness and safety to the chicken patty containing oyster mushroom.